Gait speed in older adults: exploring the impact of functional, physical and social factors - Naiara Virto; Xabier Río; Iker Muñoz-Pérez; Amaia Méndez-Zorrilla; Begoña García-Zapirain (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
Purpose: With age there is a neuromuscular and cognitive decline that impacts on functional ability. One of the most characteristic and easily recognisable signs of this decline is a decrease in usual gait speed. For older adults, gait speed is a non-invasive indicator of health and functional status and is regarded as a vital sign. As it predicts various conditions later in life, measuring usual walking speed is crucial in the clinical setting. Therefore, analysing and determining the association between walking speed and the impact of functional and socio-economic variables may facilitate the prevention of associated health problems and the maintenance of physical function in older adults. This study aims to identify the key factors that influence walking speed in older adults, as well as to examine the influence of socio-economic status on walking speed. Methods: A total of 1253 older adults (89.5% women) with a mean age of 78.1 ± 5.8 voluntarily participated in this descriptive cross-sectional study, which examines the results of functional capacity tests and socioeconomic data in older adults. To assess physical function, SPPB tests (chair stand test, balance tests, gait speed test), manual grip strength, muscle quality index, and power were conducted, in addition to measuring body composition and socioeconomic status. Results: The final regression model showed that gait speed was significantly partially explained (R2=0.35; p<0.01) by the socioeconomic environment, age, balance, and relative power. At the same time, belonging to a higher socio-economic environment is linked to lower relative power (p<0.01; η2=0.07). Conclusions: Exploring the factors that affect walking speed in older adults, this study highlights that age, relative power and balance are significant determinants. These clinical markers provide crucial information for designing personalized and effective interventions to promote healthy aging.